Monetary Reform and Central Bank Digital Currencies: The Impact on Retail Banking - Adam Abdullah (Türkiye İslam İktisadı Dergisi)
This research aims to clarify the impact of monetary reform on retail banking, with the introduction of private crypto-currencies (CCs) and retail central bank digital currencies (CBDCs). Given the exponential increase in private de-centralized CCs, involving stablecoins and non-backed digital assets, total crypto assets have now developed into a USD 1.04 trillion market capitalization. Governments and monetary authorities were initially reticent, but now a number of central banks are developing their own wholesale and retail CBDCs. By conducting library research, document and content analysis involving secondary data, this research confirms, involving central bank admission, that the current centralized monetary system allows commercial banks to lend the vast majority of deposit money into existence. However, the impact of private CCs and introduction of retail CBDCs will eliminate credit creation, thus rendering the commercial banking model obsolete. This will inevitably involve a structural change in the global financial system, with the separation of the public issuance of money and the private issuance of equity finance and investment. Ultimately, retail CBDCs will have to develop into public stablecoins that are pegged to intrinsic value to satisfy the store of value function of money and provide stability as the common denominator for all economic transactions.